Science data visualization in planetary and heliospheric contexts with 3DView. (January 2018) - Génot, V.; Beigbeder, L.; Popescu, D.; Dufourg, N.; Gangloff, M.; Bouchemit, M.; Caussarieu, S.; Toniutti, J.-P.; Durand, J.; Modolo, R.; André, N.; Cecconi, B.; et al.
Abstract: We present a 3D orbit viewer application capable of displaying science data. 3DView, a web tool designed by the French Plasma Physics Data Center (CDPP) for the planetology and heliophysics community, has extended functionalities to render space physics data (observations and models alike) in their original 3D context. Time series, vectors, dynamic spectra, celestial body maps, magnetic field or flow lines, 2D cuts in simulation cubes, etc, are among the variety of data representation enabled by 3DView. The direct connection to several large databases, the use of VO standards and the possibility to upload user data makes 3DView a versatile tool able to cover a wide range of space physics contexts. The code is open source and the software is regularly used at Masters Degree level or summer school for pedagogical purposes. The present paper describes the general architecture and all major functionalities, and offers several science cases (simulation rendering, mission preparation, etc.) which can be easily replayed by the interested readers. Future developments are finally outlined. Highlights: Java based orbit and data viewer in heliophysics and planetology science context. In-situ data, models and simulations are displayed in 3D maneuverable scenes with spacecraft and celestial objects. Uses Virtual Observatory technology to ease interoperability with other tools and databases.